1990
DOI: 10.1111/j.1365-2958.1990.tb02060.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of site‐directed mutations in the α‐and β‐subunits of Klebsiella pneumoniae nitrogenase

Abstract: Using directed mutagenesis, amino acid substitutions have been made in the alpha- and beta-subunits of the klebsiella pneumoniae nitrogenase component 1 at positions normally occupied by conserved cysteine or tyrosine residues. Nif+, Nif- and intermediate phenotypes have been obtained. To extend our earlier biochemical characterization (Kent et al., 1989) the electrophoretic mobility of component 1 of the mutant and wild-type nitrogenases has been analysed by non-denaturing gel electrophoresis. The major and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…This conclusion was based on the observation that only apo-MoFe which contained Fe (P clusters) was receptive to FeMo-co, and incorporation of such Fe required the activities of genes postulated to be involved in P cluster assembly (54). This possibility is also substantiated by amino acid substitution studies which have shown that certain altered MoFe proteins having disrupted P cluster environments do not appear to have any associated FeMo-co (9,26).…”
Section: )mentioning
confidence: 60%
“…This conclusion was based on the observation that only apo-MoFe which contained Fe (P clusters) was receptive to FeMo-co, and incorporation of such Fe required the activities of genes postulated to be involved in P cluster assembly (54). This possibility is also substantiated by amino acid substitution studies which have shown that certain altered MoFe proteins having disrupted P cluster environments do not appear to have any associated FeMo-co (9,26).…”
Section: )mentioning
confidence: 60%
“…There are five Cys residues in the NifD protein and three in the NifK protein that are conserved across nitrogenase proteins from a wide variety of nitrogen-fixing organisms (9,14); some of these Cys residues are thought to form ligands with either FeMoco or P clusters (15,16,28). Four of the five Cys residues in NifD and one of the three Cys residues in NifK are conserved in NifE and NifN, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the Mo contents and EPR spectroscopy of the mutant fractions, we propose that the loss of the P-clusters causes (i) the physical loss or inhibition of binding of some FeMoco ; (ii) the EPR and catalytic inactivation of some FeMoco ; and\or (iii) the incorporation of a FeMoco-like species into the FeMoco site of the mutant molecules. X-ray crystallographic structures of the MoFe protein [4] showed that the FeMoco clusters are bound solely to the αsubunit and that the P-clusters, as deduced from earlier sitedirected mutagenesis experiments [5], are bound at the interface of the αβ pairs of subunits. FeMoco can be considered as consisting of 4Fe-3S and 1Mo-3Fe-3S clusters which are bridged by three inorganic sulphur atoms (Figure 1, left panel).…”
Section: Introductionmentioning
confidence: 75%
“…In order to understand the structural and functional roles and relationships of FeMoco and P-clusters in nitrogenase, systematic site-directed mutagenesis programmes have been undertaken. Both conserved and non-conserved cysteine residues of the MoFe proteins of K. pneumoniae [5,11] and Azotobacter inelandii [12][13][14][15][16][17] have been replaced by other residues. One of the mutants of K. pneumoniae, pHK17, prepared in this laboratory, is unique.…”
Section: Figure 1 Structures Of Femoco (Left Panel) and P-clusters (Rmentioning
confidence: 99%
See 1 more Smart Citation